2018
DOI: 10.1016/j.nmni.2018.03.005
|View full text |Cite|
|
Sign up to set email alerts
|

Noncontiguous finished genome sequence and description of Bartonella mastomydis sp. nov.

Abstract: Bartonella mastomydis sp. nov. strain 008 is the type strain of B. mastomydis sp. nov., a new species within the genus Bartonella. This strain was isolated from Mastomys erythroleucus rodents trapped in the Sine-Saloum region of Senegal. Here we describe the features of this organism, together with the complete genome sequence and its annotation. The 2 044 960 bp long genomes with 38.44% G + C content contains 1674 protein-coding and 42 RNA genes, including three rRNA genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…None of the available biochemical tests was positive. Similar patterns have been previously observed for Bartonella senegalensis and Bartonella mastomydis [10], [24].
Fig. 4Transmission electron micrograph of Bartonella massiliensis strain OS09 T using Morgagni 268D (Philips, Amsterdam, The Netherlands) transmission electron microscope at operating voltage of 60 kV.
…”
Section: Introductionsupporting
confidence: 79%
“…None of the available biochemical tests was positive. Similar patterns have been previously observed for Bartonella senegalensis and Bartonella mastomydis [10], [24].
Fig. 4Transmission electron micrograph of Bartonella massiliensis strain OS09 T using Morgagni 268D (Philips, Amsterdam, The Netherlands) transmission electron microscope at operating voltage of 60 kV.
…”
Section: Introductionsupporting
confidence: 79%
“…Thus, our results also involve the first data about pathogens in fleas collected from the Canarian shrew. Further, as first reports of B. mastomydis (Dahmani et al 2018) were in Senegal and in Benin afterwards (Martín‐Alonso et al 2016), both located in West Africa, the presence of this species confirmed only in Lanzarote may be explained due to its proximity to this African margin.…”
Section: Discussionmentioning
confidence: 79%
“…Three strains were isolated from livers of three brush-furred rats of the genus Lophuromys (MT256381.1). Bartonella strains were cultured as previously reported [ 7 , 8 , 14 ].…”
Section: Samples and Bacterial Culturementioning
confidence: 99%
“…As previously described in similar studies [ 7 , 8 ], the internal transcribed spacer (ITS), gltA, rpoB, ftsZ and 16S ribosomal RNA (rRNA) genes were amplified and sequenced to identify isolated Bartonella strains. Three B. gabonensis isolates (strains 662, 667 and 669 T ) were obtained from three individuals of the same rodent species, the rusty-bellied brush-furred rat Lophuromys sikapusi.…”
Section: Classification and Featuresmentioning
confidence: 99%
See 1 more Smart Citation